Next-generation DNA sequencing technologies and the study of trinucleotide repeat instability - McGinty, Ryan. (2018)
Abstract: Microsatellite repeats are the source of multiple hereditary diseases in humans. Certain repetitive sequences form unusual DNA structures that differ from standard B-form DNA. As the length of a repeat increases, structures form more frequently and stably. Secondary structures can interfere with numerous cellular processes, leading to expansions and contractions of the repetitive tract, double-strand breaks (DSBs) and complex genomic rearrangements (CGRs). DNA sequencing technologies have developed in leaps and bounds in the previous decade. Large-scale DNA sequencing is now fast and inexpensive. More recently, it has become possible to sequence long stretches of DNA in a single, contiguous read. This has exciting possibilities for the study of microsatellites and CGRs, both of which are difficult to resolve using short-read sequencing technologies. I present here two innovative applications of DNA sequencing technologies used to uncover new mechanisms of microsatellite instability. In Chapter 2, short-read DNA sequencing is central to a novel screening method to identify genes involved in (GAA)n repeat expansion using yeast as a model system. This led to identification of mutants of the polyadenylation gene YSH1, later found to affect transcription-replication collisions that cause DSBs. Chapter 3 also concerns the role of transcription and the effect of nucleosome positioning on (GAA)n repeat expansions. Chapter 1 consists of a review highlighting the importance of using model systems to identify characterize modifiers of microsatellites, revealing molecular mechanisms and potentially informing human health. In Chapter 4, long-read Nanopore sequencing was used to uncover mechanisms leading to CGRs. This approach demonstrates that DNA rearrangements can be captured within individual sequencing reads, revealing the mechanisms by which DNA breakage and repair occur, including the invasion of (GAA)n repeats into other areas of the genome, recombination between repetitive transposable elements, and the use of break-induced replication. This approach can be extended not only to the further study of microsatellite instability and DNA repair, but also to cancer, where CGRs are frequent.; Thesis (Ph.D.)--Tufts University, 2018.; Submitted to the Dept. of Biology.; Advisor: Sergei Mirkin.; Committee: Catherine Freudenreich, Mitch McVey, and Shamil Sunyaev.; Keywords: Genetics, and Molecular biology.